EFEK MODERASI LOCUS OF CONTROL PADA HUBUNGAN PELATIHAN DAN KINERJA PADA BANK PERKREDITAN RAKYAT DI KABUPATEN BADUNG - Wiriani, Wayan; Piatrini, Putu Saroyeni; Ardana, Komang; Juliarsa, Gede (Jurnal Ilmiah Akuntansi dan Bisnis, 2013)
ABSTRACT This study was conducted at BPR in the Badung regency by taking a sample of 120 employees who have completed training and were divided into 4 groups. Data analysis technique used is descriptive analysis and univariate ANOVA variants assisted with SPSS version 16.0. This study aims to examine the effects of training on performance, to test the effects of locus of control on performance and examine the moderating effects of locus of control in relation training to performance. The results research shows  that of the four hypotheses proposed all showed significant differences. The main effect of training on performance   are significant that means there are  differences in average performace among employee high level training with low-level training. The main effect of locus of control  on performance are significant that means  there are significant differences in average performance of employees between the level of internal locus of control with the level of external locus of control. Interaction effect between level of training to the level of locus of control is significant that means are influence together between a training with  locus of control on the performance of employees in the BPR  of Badung  regency. The implication of this research is when companies face financial resource constraints, so can not carry out training program in high-intensity, then the company should hire employees who have internal locus of control. Companies should prioritize prospective employees who have internal locus of control in the selection  of employees and training so that training programs have been made   to improve performance. Keywords: training, internal locus of control, external locus of control, performance